Способ получения катализатора для очистки выхлопных газов двигателей внутреннего сгорания - Цикоза Л. Т.; Тарасова Д. В.; Поповский В. В.; Якушкина Л. С.; Тихова А. С.; Косинцев В. И. Виктор Иванович
опубл. 25.11.80.